Peer Edmonton Empathy Recruitment Scale (PEERS): A Tool for Student Peer Support Worker Selection and Empathy Measurement (Canadian Journal of Counselling and Psychotherapy, 2018)
Canadian universities increasingly emphasize student peer support services as a mental health treatment option. These services, composed of peer support workers (PSWs), reduce professional counselling admissions and treatment costs. The process of selecting PSWs, however, has historically been unstandardized, leading to difficulties with the assessment of ideal workers for these helping roles. To help Canadian postsecondary mental health initiatives recruit PSWs, we developed a brief nonclinical postsecondary student empathy scale that reliably identifies suitable PSWs in a student population. In this study, we discuss the strong psychometric validity and reliability of the Peer Edmonton Empathy Recruitment Scale and its utility for Canadian universities.